Risk factors analysis and prediction model construction for severe pneumonia in older adult patients - Liu, Ming-Li; Jiang, Hai-Feng; Zhang, Xue-Ling; Lu, Cai-Xia (Frontiers in Public Health, 2024)
Objective:Pneumonia is a common and serious infectious disease that affects the elderly population. Severe pneumonia can lead to high mortality and morbidity in this group. Therefore, it is important to identify the risk factors and develop a prediction model for severe pneumonia in elderly patients. Method:In this study, we collected data from 1,000 elderly patients who were diagnosed with pneumonia and admitted to the intensive care unit (ICU) in a tertiary hospital. We used logistic regression and machine learning methods to analyze the risk factors and construct a prediction model for severe pneumonia in elderly patients. We evaluated the performance of the model using accuracy, sensitivity, specificity, area under the receiver operating characteristic curve (AUC), and calibration plot. Result:We found that age, comorbidities, vital signs, laboratory tests, and radiological findings were associated with severe pneumonia in elderly patients. The prediction model had an accuracy of 0.85, a sensitivity of 0.80, a specificity of 0.88, and an AUC of 0.90. The calibration plot showed good agreement between the predicted and observed probabilities of severe pneumonia. Conclusion:The prediction model can help clinicians to stratify the risk of severe pneumonia in elderly patients and provide timely and appropriate interventions.